The effect of milling time on the microstructure and mechanical properties of Ti-6Al-4Fe alloys. (June 2021) - Fouzia, Hammadi; Mamoun, Fellah; Naouel, Hezil; Linda, Aissani; Goussem, Mimanne; Said, Mechachti; Mohammed, Abdul Samad; Alex, Montagne; Iost, Alain; Weiß, Sabine; Obrosov, Aleksei
Highlights: The effect of milling time on the Microstructure and mechanical properties of Ti-6Al-4Fe is investigated. Replacing V by Fe in Ti-6Al-4V alloys resulted in higher hardness. Increasing the milling time improved the hardness of Ti-6Al-4Fe alloys. Increasing the milling time, reduced the porosity and increased the density in the alloys. Abstract: Replacement of toxic and expensive vanadium (V) in medical grade titanium alloys with cheaper and non-toxic elements such as iron (Fe) or niobium (Nb), is an important step forward in developing safer and less expensive biomaterials. Evaluating the effect of different process parameters such as the milling time on the properties of these newly developed alloys helps in understanding and controlling their behavior. Hence, in this study, the influence of ball-milling duration (2, 6, 8, 12 and 18 h) on crystalline structure, phase evolution, densification, and mechanical characteristics of biomedical nanocrystalline Ti-6Al-4Fe (wt. %) alloys is investigated. X-ray diffraction (XRD) confirmed that after 6 h of milling, aluminum (Al) and Fe completely dissolved into Ti matrix to form a solid solution of Ti (Al, Fe). XRD further revealed that the crystallite size decreased from 56 to 30 nm and the micro-strain increased with an increase in milling time. A decrease in porosity along with an increase in density is also observed for the alloys with increasing milling time. Moreover, the values of porosity obtained for the developed Ti-6Al-4Fe alloys ranged from 1 to 12 %, which is comparable to the porosity of one of the cortical bones making it a potential candidate for bone replacements. Microhardness measurements showed that the hardness of the Ti-6Al-4Fe alloys was greater than the hardness of the conventional Ti-6Al-4V alloys. It was observed that the Ti-6Al-4Fe alloy fabricated with the powders milled for 2 h showed the lowest value of Young's Modulus. Milling time also had a significant effect on the surface roughness of the alloy samples, which showed a decreasing trend with increasing milling times.